Experimental Study on Reasonable Spacing after Carbon Dioxide Presplitting in Low-Permeability Coal Seam - Zongyong Wei; Shugang Li; Haifei Lin; Botao Li; Yang Ding; Haiqing Shuang (Advances in Civil Engineering)
Gas disasters have been always a major hidden danger that affects mining safety in coal mines. Gas drainage by drilling is the fundamental method of gas control in coal mines. In view of the low-permeability coal seam, it is the basis of the safe and efficient production of the mine to take the measures of enhancing the permeability, improving the gas drainage efficiency, and shortening the drainage time. The 4−2 coal seam of the Jianxin coal mine in Shaanxi Province of China is a low-permeability coal seam. In order to obtain the reasonable hole spacing and the reasonable extraction time after the penetration enhancement, the pressure drop method is used to investigate the extraction radius. The results show that the gas pressure around the test hole decreases with time as a negative exponential function, and the effective radius of extraction increases with the increase of extraction time as a logarithmic function. Through the comparative analysis and variance analysis of the test data of the two drilling fields, it is proved that the data of the drainage radius of the two drilling fields are accurate and reliable. It is obtained that the reasonable spacing of the gas drainage holes is 8.10 m and the reasonable drainage time is 180 days after CO2 presplitting and permeability increase in the 4−2 coal seam of the mine.